REKAYASA PERANGKAT LUNAK SELEKSI PENENTUAN VENDOR JASA TENAGA KERJA DENGAN METODE SAW - Edy Nasri; Kania Kania (Teknik Informatika Fakultas Ilmu Komputer, 2019)
Information technology that is growing rapidly, especially computer technology (software and hardware) is widely used as a tool by users in the form of individuals and companies to help complete the operational production work every day. Labor service vendor selection auction system is needed by various companies to speed up the vendor selection process, especially in the administration section. The process of selecting vendor auctions today is still using a conventional system, so that selection selection decisions for vendor selection are less than quality causing the process to be less than optimal. So this research was conducted to make a software engineering that can help companies in the selection process of labor service vendor selection. For this solution, we use the Simple Additive Weighting (SAW) method as the method of resolution and so that applications are made safer and easier to maintain the system, application development using the PHP Webbase Programming Language with Laravel Framework and Postgresql Database.